The human experience of ethics: a review of a decade of qualitative ethical decision‐making research. (6th September 2016) - Lehnert, Kevin; Craft, Jana; Singh, Nitish; Park, Yung‐Hwal
Abstract : Qualitative studies are an important component of business ethics research. This large amount of research covers a wide array of factors and influences on ethical decision making published between 2004 and 2014. Following the methodology of past critical reviews, this work provides a synopsis of the diverse array of qualitative studies in ethical decision making within the business ethics literature. We highlight the distinct and investigative nature of qualitative research, synthesize and summarize findings, and suggest opportunities for future research. We conclude with a recommendation for developing qualitative studies in business ethics and a call for an increased openness when considering this valuable and underrepresented strategy of inquiry.